2022
DOI: 10.1038/s41598-022-05296-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic data sharing and artificial intelligence in the era of personalized medicine based on a cross‐sectional analysis of the Saudi human genome program

Abstract: The success of the Saudi Human Genome Program (SHGP), one of the top ten genomic programs worldwide, is highly dependent on the Saudi population embracing the concept of participating in genetic testing. However, genetic data sharing and artificial intelligence (AI) in genomics are critical public issues in medical care and scientific research. The present study was aimed to examine the awareness, knowledge, and attitude of the Saudi society towards the SHGP, the sharing and privacy of genetic data resulting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 37 publications
0
15
0
2
Order By: Relevance
“…We should agree with foreign authors in that medical confidentiality is a subject for disputes, as it is necessary to protect a patient's privacy and, at the same time, bear responsibility for preserving other people's health (Raimundo, Grando, Machado, Oliveira, Cabar, 2022). The regime of personal data protection is of particular concern due to their vulnerability, probable illegal actions, discrimination, and unethical illegal use (Alrefaei, A.F., Hawsawi, Y.M., Almaleki, D. et al, 2022). At the same time, the polls on personalized medicine held in Pennsylvania (USA) and Bavaria (Germany) showed that most of the respondents were concerned about misuse of genetic data (Kichko, K., Marschall, P.&Flessa, S., 2016).…”
Section: Personal Data: Conceptmentioning
confidence: 98%
“…We should agree with foreign authors in that medical confidentiality is a subject for disputes, as it is necessary to protect a patient's privacy and, at the same time, bear responsibility for preserving other people's health (Raimundo, Grando, Machado, Oliveira, Cabar, 2022). The regime of personal data protection is of particular concern due to their vulnerability, probable illegal actions, discrimination, and unethical illegal use (Alrefaei, A.F., Hawsawi, Y.M., Almaleki, D. et al, 2022). At the same time, the polls on personalized medicine held in Pennsylvania (USA) and Bavaria (Germany) showed that most of the respondents were concerned about misuse of genetic data (Kichko, K., Marschall, P.&Flessa, S., 2016).…”
Section: Personal Data: Conceptmentioning
confidence: 98%
“…Technology advancements have made it clear that numerous genes, including BRCA1/2 and BARD1, play a crucial role in hereditary and familial breast cancer and ovarian cancer [18,19]. Research has identified BARD1's function in the BRCA1dependent pathway as an anti-breast cancer agent [20].…”
Section: Bard1 As a Tumor-suppressor Gene And Oncogenementioning
confidence: 99%
“…Many genetic programmes are hailed for delivering medical breakthroughs via personalised medicine and the diagnosis of hereditary diseases. For instance, the Saudi Human Genome Program (SHGP), launched by the Saudi King in 2013, was announced with such aims (Alrefaei et al 2022). Research showed that "90.7% of [Saudi] participants agreed that AI could be used in the SHGP" (ibid).…”
Section: Case 2: Genetic Privacymentioning
confidence: 99%